Monitoring Algorithm for Electrical Variables Implementing Blockchain and Python - Muñoz-Romero, Javier Andres; Giral-Ramírez, Diego Armando; Ramírez-Vanegas, Carlos Alberto (Tecnura, 2022)
ABSTRACT Objective: This article presents a blockchain application in power systems using electrical variable monitoring delivered by a simulated relay. Methodology: The electrical variables are verified, compared, and uploaded to a blockchain network created by a network of servers. These are responsible for uploading, validating, and exporting information to the algorithm. This study is carried out by means of the Python programming language. Results: An algorithm capable of integrating these variables from a simulated relay is created, as well as four servers in charge of taking the relay signals every minute, validating that they are unique in the blockchain and uploading them. The first node that completes this task uploads its identification and the information of the relay. Once obtained, the information processing times are approximately 10 seconds. Conclusions: It is concluded that the algorithm is capable of decentralizing the information collected by the servers in times equal to or greater than one minute, which can be very useful when saving information. In applications such as control by the network operator, it falls short by having times higher than or equal to one minute. It should be taken into account that, for the development of a blockchain with a greater number of equipment, it is advisable to use machines with high levels of processing and much greater RAMs. These characteristics would allow the algorithm to run smoothly and in the shortest time possible. Financing: Universidad Distrital Francisco José de Caldas